Transverse Incision for Pancreatoduodenectomy Reduces Wound Complications: A Single-Center Analysis of 399 Patients - Junker, Stefanie; Jacobsen, Anne; Merkel, Susanne; Denz, Axel; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Journal of Clinical Medicine, 2023)
Background: Even if the minimally invasive approach is advancing in pancreatic surgery, the open approach is still the standard for a pancreatoduodenectomy. There are two types of incisions used: the midline incision (MI) and transverse incision (TI). The aim of this study was to compare these two incision types, especially regarding wound complications. Methods: A retrospective review of 399 patients who underwent a pancreatoduodenectomy at the University Hospital Erlangen between 2012 and 2021 was performed. A total of 169 patients with MIs were compared with 230 patients with TIs, with a focus on postoperative fascial dehiscence, postoperative superficial surgical site infection (SSSI) and the occurrence of incisional hernias during follow-up. Results: Postoperative fascial dehiscence, postoperative SSSI and incisional hernias occurred in 3%, 8% and 5% of patients, respectively. Postoperative SSSI and incisional hernias were significantly less frequent in the TI group (SSI: 5% vs. 12%, p = 0.024; incisional hernia: 2% vs. 8%, p = 0.041). A multivariate analysis confirmed the TI type as an independent protective factor for the occurrence of SSSI and incisional hernias (HR 0.45 (95% CI = 0.20–0.99), p = 0.046 and HR 0.18 (95% CI = 0.04–0.92), p = 0.039, respectively). Conclusion: Our data suggest that the transverse incision for pancreatoduodenectomy is associated with reduced wound complications. This finding should be confirmed by a randomized controlled trial.
CRIS-Team Scopus Importer:2023-05-12
Keywords: fascial dehiscence; incisional hernia; midline incision; pancreatoduodenectomy; surgical site infection; transverse incision